Rechazo al cuidado de la salud por motivaciones del paciente (2010)
ABSTRACT: To describe the meaning for the patients of the health care rejection. Methodology. Qualitative study with phenomenological focus performed in Medellin (Colombia) between 2008 and 2009. It included 12 hospitalized adults. The in depth interview was used to collect the information. Data were analyzed according to the Cohen, Kahan and Steeves proposed scheme. Results. Fear, suffering, dependency as well as the “bad reputation” of professionals, institutions or procedures contribute to the answer to care rejection. Patients reject the disease because of pain and suffering. Knowledge plays a double role in health care because it helps to accept or reject care and promote patients’ acceptance and satisfaction. Conclusion. Rejection is a patient decision answering to situations linked to the disease, knowledge and nurses’ behaviors should be taken into account by the nurses.